(3QSGdI aj GdJhMjOs
(3ChdgG (B:s
(3eG bhdce QVj Gddg Yfce aj oCfGS f Ggd GdSfI hGdLeGYI dGjDPhf dUdGI jhe GdLeYI EdG CPf hGMO EPG UYO GdEeGe Ydi GdefHQ s
(3BNQgG (B:s
(3GdMb dGjJLGhR YeG aj gPg GdQSGdI ceG dGjNaj Ydi Phj GdQTO hGdYOGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B29s
(3hQOJ CjVkG JMJ Qbe (B28/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(D 404) s
Keywords: (3GdJhMjO hGdedd hGdfMds